Emergency and Trauma Imaging of the Thoracolumbar Spine - Moutinho, Ricardo; Tyrrell, Prudencia; Cassar-Pullicino, Victor N. (Seminars in Musculoskeletal Radiology, 2017)
Spine trauma is a devastating event with high morbidity and mortality and many additional medical, psychological, social, and financial consequences for patients, their families, and society. The thoracolumbar spine represents the most common area fractured in the spine. Morphology, extent, and the location of fracture lines are important determinants of stability, which is the core issue in the assessment of vertebral injuries, dictating conservative or surgical treatment. After hospital admission and clinical stabilization, patients with potential spine trauma are screened radiologically. Imaging analysis is based on radiographs, computed tomography, and magnetic resonance imaging. Understanding these three tools is essential to get a clear picture of the extent of any vertebral fracture. A multidisciplinary team should provide assessment, treatment, and education to patients with a spinal injury to achieve a treatment tailored for each patient. Thoracolumbar trauma focusing on spinal biomechanics, stability, imaging modalities, morphology patterns, classifications, and treatment are discussed and reviewed.
Keywords: thoracolumbar spine trauma; stability; CT; MRI; morphology patterns; treatment